Antivirals for influenza-Like Illness? A randomised Controlled trial of Clinical and Cost effectiveness in primary CarE (ALIC4 E): the ALIC4 E protocol. Issue 7 (12th July 2018) - Bongard, Emily; van der Velden, Alike W; Cook, Johanna; Saville, Ben; Beutels, Philippe; Munck Aabenhus, Rune; Brugman, Curt; Chlabicz, Slawomir; Coenen, Samuel; Colliers, Annelies; Davies, Melanie; De Paor, Muireann; et al.
Abstract : Introduction: Effective management of seasonal and pandemic influenza is a high priority internationally. Guidelines in many countries recommend antiviral treatment for older people and individuals with comorbidity at increased risk of complications. However, antivirals are not often prescribed in primary care in Europe, partly because its clinical and cost effectiveness has been insufficiently demonstrated by non-industry funded and pragmatic studies. Methods and analysis: Antivirals for influenza-Like Illness? An rCt of Clinical and Cost effectiveness in primary CarE is a European multinational, multicentre, open-labelled, non-industry funded, pragmatic, adaptive-platform, randomised controlled trial. Initial trial arms will be best usual primary care and best usual primary care plus treatment with oseltamivir for 5 days. We aim to recruit at least 2500 participants ≥1 year presenting with influenza-like illness (ILI), with symptom duration ≤72 hours in primary care over three consecutive periods of confirmed high influenza incidence. Participant outcomes will be followed up to 28 days by diary and telephone. The primary objective is to determine whether adding antiviral treatment to best usual primary care is effective in reducing time to return to usual daily activity with fever, headache and muscle ache reduced to minor severity or less. Secondary objectives include estimating cost-effectiveness, benefits in subgroups according to age (<12, 12–64 and >64 years), severity of symptoms at presentation (low, medium and high), comorbidity (yes/no), duration of symptoms (≤48 hours/>48–72 hours), complications (hospital admission and pneumonia), use of additional prescribed medication including antibiotics, use of over-the-counter medicines and self-management of ILI symptoms. Ethics and dissemination: Research ethics committee (REC) approval was granted by the NRES Committee South Central (Oxford B) and Clinical Trial Authority (CTA) approval by The Medicines and Healthcare products Regulatory Agency. All participating countries gained national REC and CTA approval as required. Dissemination of results will be through peer-reviewed scientific journals and conference presentations. Trial registration number: ISRCTN27908921 ; Pre-results.